2021
DOI: 10.1371/journal.pone.0257385
|View full text |Cite
|
Sign up to set email alerts
|

Noncommunicable diseases risk factors in Bhutan: A secondary analysis of data from Bhutan’s nationwide STEPS survey 2014

Abstract: Background Bhutan is facing an epidemic of noncommunicable diseases; they are responsible for 53% of all deaths. Four main modifiable risk factors, including tobacco use, harmful use of alcohol, physical inactivity, and unhealthy diet, are the causes of most noncommunicable diseases (NCDs). This study aimed to assess 1) the prevalence of NCDs modifiable risk factors in Bhutan’s adult population and 2) associations between the sociodemographic factors and the NCDs modifiable risk factors with overweight or obes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…Lifestyle changes, population ageing, globalization and urbanization are the predominant key drivers of the increase of chronic diseases [ 6 ]. Consistent with previous study [ 7 ] found that the prevalence of NCD modifiable risk factors such as overweight or obesity and hypertension was high in Bhutan.…”
Section: Introductionsupporting
confidence: 92%
“…Lifestyle changes, population ageing, globalization and urbanization are the predominant key drivers of the increase of chronic diseases [ 6 ]. Consistent with previous study [ 7 ] found that the prevalence of NCD modifiable risk factors such as overweight or obesity and hypertension was high in Bhutan.…”
Section: Introductionsupporting
confidence: 92%
“…Furthermore, since the main source of alcohol is home-brewed Ara, "intervention targeting a reduction in the production of the local alcohol Ara should be undertaken urgently" [SIC] (34). We also found an increase in the prevalence of inadequate fruit and vegetable consumption, which may be due to seasonal availability, dietary habits (8), and the decline in fruit production (35). The government can increase interventions in terms of body weight control, tobacco use cessation, reduction of alcohol use, healthy eating, and screening and control of high levels of blood glucose, cholesterol, and blood pressure.…”
Section: Discussionmentioning
confidence: 87%
“…Early screening targeting men, urban dwellers, and those with higher education should be promoted to prevent risk factors for NCDs in Bhutan. Compared to the 2013 Nepal paper, this study showed a higher rate of current tobacco use (24.8% in 2014) than in Nepal (18.5%), low physical activity (11.9% in 2014) than Nepal (3.4%), higher obesity (≥25 kg/m 2 , 32.9% in 2014) than Nepal (≥25 kg/m 2 , 21.4%), elevated blood pressure (35.7% in 2014) than Nepal (25.7%), and a lower rate of inadequate fruit and vegetable intake (66.9% in 2014) than Nepal (98.9%) ( 8 ), lower elevated blood glucose (2.3% in 2014) than Nepal (3.6%), and lower elevated total cholesterol (12.5% in 2014) than Nepal (22.7%) ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical inactivity is also one of the main preventable causes of mortality worldwide as it is a modifable risk factor for chronic diseases such as cardiovascular disease, hypertension, type 2 diabetes mellitus, depression, cancers, and obesity [13][14][15][16]. Sedentary lifestyle would increase the chance of being overweight and obese, and both have an additive impact on the increasing prevalence of noncommunicable diseases in populations [17][18][19]. Along with unhealthy habits like smoking and environmental risk factors, physical inactivity will eventually lead to higher odds of morbidity and mortality due to preventable causes, which puts a considerable burden on healthcare systems, especially in older ages [20,21].…”
Section: Introductionmentioning
confidence: 99%